Object shift in Romance - Gallego, Angel J (Natural language and linguistic theory, 2013)
This paper discusses the properties of VOS sentences in Romance and their bearing on Case assignment, verb movement, parametric variation, and the structure of the vP periphery / low IP area. The literature on Romance VOS has argued that this order is derived either through object shift (Ordóñez 1997, 1998, 2000) or VP fronting (Belletti 2001, 2004; Zubizarreta 1998), providing empirical evidence in support of both derivations. In this paper, I focus on various aspects of VOS sentences in Romance languages. First, I argue that both object shift and VP-fronting strategies are actually available, but subject to a very specific parametric cut: Western Romance languages (Galician, European Portuguese, and Spanish) resort to object shift, whereas Central-Eastern varieties (Catalan and Italian) fail to do so, requiring the VP-fronting derivation instead (López 2009a). Second, I put forward a previously unnoticed generalization that reveals that only those varieties licensing object shift based VOS can generate VSO sentences, which I refer to as the VOS-VSO Generalization. Finally, I claim that object shift in VOS sentences of Western Romance languages displays a cluster of unnoticed properties that pattern with Scandinavian-style object shift (Bobaljik and Jonas 1996; Bobaljik and Thráinsson 1998; Collins and Thráinsson 1996; Holmberg 1986, 1999; Vikner 2006), thus obeying Holmberg's Generalization (Holmberg 1986, 1999). If on track, the present account not only reveals interesting syntactic similarities between Scandinavian and Romance object shift, but also reinforces a well-known micro-parameter that disentangles Western from Central-Eastern Romance languages.